How important are land prices to promote smart mobility? - Emília Malcata Rebelo (2013)
This paper researches and proposes an objective way to compute land prices, based on their real and current values, and not on speculative grounds. This general concern falls within the framework of the overall revision of the Portuguese Land Use Law currently taking place, that pursues the following goals: to assure citizensŽ access to housing (preventing real estate speculation); to control urban development processes, and to recover a significant slice of vacant dwellings; to ensure an increased transparency in urban processes, and a deeper involvement of citizens; and to return the surplus-values accrued from public interventions for the benefit of the society in general. The methodology proposed in this research founds on the Real Estate Municipal Tax Code - that was applied to the Municipality of Bragança - in order to determine the average price of land/m2 according to the location and uses anticipated by the Municipal Master Plan (within the categories of developed land and land which development may be programmed, both aimed at built-up spaces). The comparison between the values attained and the homologous market values show up that the former are substantially lower than the latter. So the enforcement of the new Land Use Law that tentatively includes the application of the current methodology, together with other proposals - stresses the importance of this law-supported objective way to assess land prices. It straight reflects into the anticipated costs of urban development, construction initiatives, and transport infrastructures, and into the costs involved in the implementation of accessibility and mobility measures. It consequently, exerts an important impact on the promotion of smart mobility for the municipalityŽs population.